Building the blueprint: Formulating a community‐generated national plan for future research in inherited bleeding disorders. Issue 5 (14th June 2022) - Valentino, Leonard A.; Witkop, Michelle L.; Santaella, Maria E.; DiMichele, Donna; Recht, Michael
Abstract: Introduction: Decades of inherited bleeding disorders (BD) research transformed severe haemophilia from a childhood killer to a disorder managed across a full lifespan for many in economically developed countries. Health equity, a life unimpaired by disease complications, however, remains unimaginable for most people with an inherited BD (PWIBD). Aim: The National Hemophilia Foundation (NHF) and American Thrombosis and Hemostasis Network (ATHN) undertook the development of a community‐driven United States (US) National Blueprint for Inherited Bleeding Disorders Research to transform the experience of all PWIBD and those who care for them. Methods: Extensive community consultations were conducted to identify the issues most important to PWIBD and those who love and care for them. Expert multidisciplinary teams distilled these key areas of need into prioritised research questions, and identified the resources and infrastructure required to pursue them. A summit was held to gather feedback and inform the detailed blueprint. Results: Community‐prioritised research areas fell into three broad categories: issues common across inherited BDs, those specific to individual disorders, and issues of infrastructure and capacity. NHF State of the Science Research Summit discussions of the research questions derived from the community priorities by six working groups provided important input for the drafting of the research blueprint for the coming decades. Conclusion: The inherited BD community came together to develop the US National Blueprint for Inherited Bleeding Disorders Research dedicated to transforming the lives of all PWIBD including innovating solutions for the rarest disorders and under‐represented populations.